SISTEM INFORMASI AKADEMIK SMK NEGERI 3 SUMBAWA BESAR BERBASIS WEB - Reza Sangga Rasefta; Shinta Esabella (Program Studi Informatika Universitas Teknologi Sumbawa, 2020)
This study aims to design and build a Web-Based Academic Information System of SMK Negeri 3 Sumbawa in order to (1) Assist Curriculum section work in managing school academic information which was previously still manual by printing and pasting on the bulletin board, so that the information system built makes curriculum part work is more effective and efficient. (2) Facilitate students and teachers in obtaining schoolrelated academic information such as student data, teacher data, lesson schedules, value data whenever needed. This research belongs to descriptive qualitative research. The use of descriptive type is intended as a problem-solving procedure that is investigated by describing the state of the subject and object under study at present based on facts that are visible and as they are. Development of information systems with PHP programming languages and MySQL databases. In this study using the method of software development extreme programming, data collection methods with observation, interviews, and literature studies, system modeling using a structured model namely ERD (Entity Relationship Diagram) and DFD (Data Flow Diagram), while testing the system with the black box method testing is testing the system in terms of functionality.